Features of Memory-Like and PD-1+ Human NK Cell Subsets - Della Chiesa, Mariella; Pesce, Silvia; Muccio, Letizia; Carlomagno, Simona; Sivori, Simona; Moretta, Alessandro; Marcenaro, Emanuela (Frontiers in Immunology, 2016)
Human NK cells are distinguished into CD56brightCD16− cells and CD56dimCD16+ cells. These two subsets are conventionally associated with differential functional outcomes and are heterogeneous with respect to the expression of KIR and CD94/NKG2 heterodimers that represent the two major types of HLA-class I-specific receptors. Recent studies indicated that immature CD56bright NK cells, homogeneously expressing the inhibitory CD94/NKG2A receptor, are precursors of CD56dim NK cells that, in turn, during their process of differentiation, lose expression of CD94/NKG2A and subsequentially acquire inhibitory KIRs and LIR-1. The terminally differentiated phenotype of CD56dim cells is marked by the expression of the CD57 molecule that is associated with poor responsiveness to cytokine stimulation, but retained cytolytic capacity. Remarkably, this NKG2A−KIR+LIR-1+CD57+CD56dim NK cell subset when derived from individuals previously exposed to pathogens, such as human cytomegalovirus (HCMV), may contain “memory-like” NK cells. These cells are generally characterized by an upregulation of the activating receptor CD94/NKG2C and a downregulation of the inhibitory receptor Siglec-7. The “memory-like” NK cells are persistent over time and display some hallmarks of adaptive immunity, i.e., clonal expansion, more effective antitumor and antiviral immune responses, longevity, as well as given epigenetic modifications. Interestingly, unknown cofactors associated with HCMV infection may induce the onset of a recently identified fully mature NK cell subset, characterized by marked downregulation of the activating receptors NKp30 and NKp46 and by the unexpected expression of the inhibitory PD-1 receptor. This phenotype correlates with an impaired antitumor NK cell activity that can be partially restored by antibody-mediated disruption of PD-1/PD-L interaction.